Sistem Pengelolaan Ruang Parkir Berbasis Internet Of Things (IoT) - Rony Setiawan (Yayasan Nuraini Ibrahim Mandiri, 2024)
This research aims to design and implement an Internet of Things (IoT)-based parking management system that can monitor and control the usage of parking spaces in real-time. The system utilizes load cell sensors to detect the availability of parking spaces and sends the data to a central server via the internet. The availability information can then be accessed by users through a mobile application. With this system, it is expected to reduce the time drivers spend searching for parking spaces and improve the efficiency of parking space management. The research employs a prototype methodology, which includes stages such as system development, hardware and software development, and system testing. The hardware used includes the ESP-WROOM-32 as the microcontroller, load cell sensors for object detection, a Liquid Crystal Display (LCD) to provide parking space information, and LEDs as indicators for each parking space. The software is developed using Arduino IDE for microcontroller programming and XAMPP as the web server.